Biophysical Investigations of the Specificity between Rab GTPases and their Effectors - KEARNEY, AOIFE MAIREAD (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
The specificity of protein-protein interactions is a complex process that is poorly understood and difficult to predict. Understanding the molecular basis for specificity of a protein and its binding partner requires a structural analysis of the interactions in the complex. However, static X-ray structures still do not reveal the thermodynamic basis for molecular recognition, nor the key contacts that provide specificity in recognition. Rab proteins are an intriguing case study as the Rabs display a high level of structural similarity amongst members. Despite this, Rabs bind many structurally diverse effectors with exquisite specificity. The main topic of this thesis, the Rab11 subfamily which includes Rab25, binds to a class of effectors termed the Rab11 Family of Interacting Proteins (FIPs). These effectors have been shown to have variable affinities for Rab11/25. Interestingly, some of the FIPs also bind to Rab14, which is an evolutionarily more distant relative. Despite the known crystal structures of Rab11 and Rab14 with their cognate FIPs, the structural basis for the distinct affinities are not apparent. Moreover, Rab14 can recognise a sub-family of FIPs (Class I) but cannot bind to Class II FIPs, while the Rab11 proteins can effectively bind to all FIPs. The cellular functions of Rab11 and Rab14 are independent and our hypothesis is that our thermodynamic and structural analyses may provide insight into their different cellular functions. Through a series of mutagenesis and binding studies, we identify sites in Rab11 that are unrelated to interfacial residues that can influence the affinities of interactions with class I FIPs. Further, we examine the structure of a class I FIP, FIP2, independent of its cognate Rab. No crystal structure of an uncomplexed FIP effector is present in the literature. We hypothesise that structure of FIP2 in solution is different to that formed under the conditions of the complex and that Rab binding may capture a particular conformation of the FIP2 molecule. This thesis provides insight into the specificity of effectors for Rab GTPases and their cellular functions in cells. We show that small changes in sequence and structure of a Rab may dictate its affinity for a given effector and determine preferential formation of one complex over another.
APPROVED
Keywords: Rab, Vesicle Trafficking, Rab11, Rab14